Single-Sex Schooling at an Elite Independent School: A Multi-Methods Case Study - Robinson, Daniel B.; Hadley, Gregory R. L.; Mitton, Jennifer (Alberta Journal of Educational Research, 2024)
This article focuses upon the milieu of single-sex schooling within an elite independent school in a Canadian urban centre. This research served as an exploratory and critical examination of single-sex schooling in a specific context, and considered its relevance, pedagogical effectiveness, and ability to meet its purported goals. Using an interpretative methodological framework, and employing a multi-methods case study design, the purpose of this research was to investigate the strengths, limitations, and possibilities of single-sex schooling in a particular educational context as informed by its students, parents of students, graduates, and teachers. We found little evidence to support the idea that single-sex schooling overwhelmingly impacted student academic or social development. Implications for practice at schools offering single-sex schooling are addressed and focus upon the importance of gender-inclusive schooling; the school as the key, rather than the school’s single-sex classes; and addressing boys’ behaviour.